THE SOURCES OF OUTCOMES IN OUTCOMES BASED EDUCATION CURRICULUM DEVELOPMENT: A CLOSER LOOK - Cahapay, Michael B (PUPIL: International Journal of Teaching, Education and Learning, 2021)
Outcomes Based Education, widely known as OBE, has become a curriculum byword across the disciplinary spectrum in higher education. However, despite the growing scholarly effort to account for the processes undertaken in developing a curriculum that is hinged on the outcomes, a functional synthesis of the sources of outcomes has not been made. This paper attempted to synthesize the sources of outcomes drawn from the field. Following the systematic review method, relevant studies were searched, collected, and analyzed. It emerged in the result that multiple sources were considered in making decisions about the outcomes. These sources of outcomes include regulatory bodies, institutional philosophy, industry demands, subject matter experts, curriculum benchmarks, and learning frameworks. It further found out that, in considering particular sources of outcomes in curriculum development, the unique contexts play an essential role. Thus, it is recommended that an examination of the experiences, resources, and demands should be carefully made, so that appropriate sources of outcomes may be considered. The implications to theory, practice, and research are discussed in the paper.